Output Feedback Adaptive Decentralized Control of Cooperative Robots - Sadati, Nasser (2007)
In this paper a decentralized control scheme for multiple cooperative manipulators is developed to achieve the desired performance in motion and force tracking, in the presence of uncertainties in dynamic equations of the robots. To eliminate the effects of uncertainties in the closed-loop performance, a new adaptive control algorithm is proposed. Based on the Lyapunov stability method, it is proved that all the error signals in the closed-loop system which is compose of a robot, an observer and a controller asymptotically converge to zero. Also to avoid the difficulties of using velocity sensors within the cooperative system, an output feedback control scheme with a linear observer is used.